Enhancement of output power level of RF energy harvesting circuit using Wilkinson power combiner. Issue 1 (2nd January 2023) - Banerjee, Joydeep
ABSTRACT: Different interesting research has been going on in the area of RF energy harvesting during the last decade. This paper presents the comparisons of different Schottky diode-based RF energy harvester circuits and cross-coupled MOS-based RF energy harvester circuits. An improvement at output power level is achieved. In this proposed work, the author has proposed a simple two-way Wilkinson power combiner to connect with these RF energy harvesting circuits for achieving a higher power level. The experimental output voltage of a three-stage diode-based Villard RF energy harvester circuit has been carried out. A Schottky diode-based Villard RF energy harvester circuit is tested at 600 MHz, and output voltage has been carried out. The circuit is also connected at 2.4 GHz Wi-Fi. A Monte Carlo simulation was also carried out to analyse the output parameters obtained from this proposed MOS-based circuits.